Characterization and Secretory Expression of a Thermostable Tannase from Aureobasidium melanogenum T9: Potential Candidate for Food and Agricultural Industries - Liu, Lu; Guo, Jing; Zhou, Xue-Feng; Li, Ze; Zhou, Hai-Xiang; Song, Wei-Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Being a key industrial enzyme, tannase is extensively applied in various fields. Despite the characterizations of a large number of tannases, there are hardly a few tannases with exceptional thermostability. In this detailed study, a tannase-encoding gene named tanA was identified from Aureobasidium melanogenum T9 and heterologously expressed in Yarrowia lipolytica host of food-grade. The purified tannase TanA with a molecular weight of above 63.0 kDa displayed a specific activity of 941.4 U/mg. Moreover, TanA showed the optimum activity at 60 °C and pH 6.0. Interestingly, TanA exhibited up to 61.3% activity after incubation for 12 h at 55 °C, signifying thermophilic property and distinguished thermostability. Additionally, TanA was a multifunctional tannase with high specific activities to catalyze the degradation of various gallic acid esters. Therefore, this study presents a novel tannase, TanA with remarkable properties posing a potential candidate for food and agricultural processing.